KESETARAAN GENDER DALAM POLITIK KAMPUS : KAJIAN KRITIS PERSPEKTIF FEMINISME: Studi Kritis Feminisme tentang Politik Kampus dan Kepemimpinan Perempuan - Nisrina, Risa; Aulia, Rahma; Ammar Yazid, Muhammad; Nurhakiki, Afiyata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines the dynamics of gender equality within campus politics by focusing on leadership, representation, and the experiences of women in student organizations. Using a descriptive qualitative approach, the research explores how social constructions, patriarchal culture, and representational practices shape power relations within student organizational spaces. The study employs Mary Wollstonecraft’s classical feminist theory, Judith Butler’s contemporary gender theory, and Stuart Hall’s representation framework to identify forms of subordination, negotiation, and resistance experienced by women. The analysis draws on previous studies, journal articles, and empirical findings regarding women’s political participation in higher education. The results indicate that women continue to face structural barriers such as masculine leadership stereotypes, gender-based division of labor, and limited institutional support. However, various studies show that women are able to establish more inclusive and participatory collaborative leadership patterns, playing an important role in strengthening democratic culture on campus. Furthermore, contemporary Islamic theological perspectives suggest that the principle of gender equality has strong normative foundations that support women’s participation in public spaces. This study affirms the importance of organizational cultural transformation, the strengthening of gender-based political education, and the mainstreaming of feminist perspectives in order to create a campus political environment that is more equal, inclusive, and just for all students.